Ferning and Schirmer Test 1 for the Detection of Grading Severity of Dry Eye Syndrome in Post Phacoemulsification Patients - Zubaidah, Tengku Siti Harilza; Lubis, Rodiah Rahmawaty; Feriyawati, Lita (Folia Medica Indonesiana, 2022)
Highlights: 1. Females were the most gender who suffer from dry eye syndrome than males. 2. Undergone phacoemulsification patients had frequent dry eye syndrome. 3. Post-phacoemulsification patients were not statistically significant between the Ferning and the Schirmer test. Abstract: Dry eye syndrome is a multifactorial disease on the surface of the eyeball characterized by loss of tear film homeostasis, which is associated with eye symptoms, where there is tear instability and hyperosmolarity, inflammation, and damage to the surface of the eye, as well as neurosensory disorders that act as the cause of this syndrome. The aim of this study was to identify relationship between the Ferning pattern and the Schirmer test 1 in post-phacoemulsification patients. The design of this study was an analytical observational study with a cross-sectional data collection method where the Ferning and Schirmer test 1 were examined to determine the severity of dry eye syndrome in post-phacoemulsification patients. The Ferning test was assessed according to Rolando's classification. In this study, it was found that the gender who suffer from dry eye syndrome are women. The most considerable age is age â‰¥ 60 years (56,7%). The results showed that the majority of patients experienced dry eyes measured with the Ferning test, and these results were following the previous Schirmer Test 1 examination. The Ferning and Schirmer tests were found to be abnormal in most of the subjects. It was found that there was a significant relationship between the Ferning pattern and the Schirmer test with the calculation of the t-value of 7.345 with a p-value of 0.001. There was a statistically significant difference between the results of Ferning and the Schirmer test in post-phacoemulsification patients.